Platelets and Immune Responses During Thromboinflammation - Mezger, Matthias; Nording, Henry; Sauter, Reinhard; Graf, Tobias; Heim, Christian; von Bubnoff, Nikolas; Ensminger, Stephan M.; Langer, Harald F. (Frontiers in Immunology, 2019)
Besides mediating hemostatic functions, platelets are increasingly recognized as important players involved in inflammation. Data from experiments in mice and men revealed various points of intersection between thrombosis, hemostasis and inflammation, which are addressed and discussed in this review in detail. One such example is the intrinsic coagulation cascade that is initiated after platelet activation thereby further propagating and re-enforcing wound healing or thrombus formation, which contributes to the pathophysiology of severe diseases. FXII of the intrinsic pathway connects platelet activation with the coagulation cascade during immune reactions. It can activate the contact system thereby either creating an inflammatory state or accelerating inflammation. Recent insights into platelet biology could show that platelets are equipped with complement receptors. Platelets are important for tissue remodeling after injury has been inflicted to the endothelial barrier and to the subendothelial tissue. Thus, platelets are increasingly recognized as more than just cells relevant for bleeding arrest or thrombus formation, and further interesting insights into platelet biology are to be discovered. In the future this understanding will potentially offer novel opportunities for therapeutic intervention in diseases, where platelets are involved.